LABORATORY MEASUREMENTS AND MODELING OF METAL-HUMIC INTERACTIONS UNDER ESTUARINE CONDITIONS - Hamilton-Taylor J.; Postill A.S.; Tipping E.; Harper M.P. (My University, 2002)
Equilibrium dialysis was used to measure Co- and Cu-binding by an isolated peat humic acid (PHA) in controlled laboratory experiments under simulated estuarine conditions: ionic strengths of 0.005 to 0.7 M in NaCl and mixed Na-Mg-Ca chloride solutions, with trace metal concentrations of ~5 x 10-7 M, a PHA concentration of 10 mg/L, and at constant pH values of ~7.8 (Co and Cu) and ~4.6 (Cu only). Generally, Co- and Cu-humic binding decreased substantially with increasing ionic strength and, in the case of Cu, with decreasing pH. The presence of seawater concentrations of Ca and Mg had a relatively small effect on Co-humic binding and no measurable effect on that of Cu under the experimental conditions. The binding data were well-described by an equilibrium speciation code (the Windermere Humic Aqueous Model, WHAM) after optimising the fits by varying the metal-proton exchange constants for humic acid within justifiable limits (i.e., within 1 standard deviation of the mean exchange constants used in the WHAM database). The main factor producing the observed variations in metal-humic binding at constant pH was the electrostatic effect on the humic molecule. WHAM was used to predict Co- and Cu-humic binding in simulations of real estuaries. Co-humic binding is predicted to be relatively unimportant (generally <5% of total Co), whereas the Cu-humic complex is likely to be the dominant species throughout an estuary. The main factors producing changes in Co- and Cu-humic binding in the real-estuary simulations are the electrostatic effect on the humic molecule, ligand competition (mainly from carbonate species) for metals, and to a lesser extent Ca and Mg competition for humic binding sites. Variations in pH are significant only at the freshwater end of an estuary. WHAM simulations also indicated that competition effects between metals are more likely to occur in freshwaters than in seawater, due to enhanced electrostatic binding at low ionic strength.